Comparison of the predictive capability of antral follicle count vs. the anti-Müllerian hormone for ovarian response in infertile women - Sun, Xingyu; Xiong, Wang; Liu, Liting; Xiong, Junjun; Liao, Chenlu; Lan, Yunzhu; Li, Feifei; Tao, Shufei; Meng, Muzi; Sun, Chenyu; Mao, Xiguang (Frontiers in Endocrinology, 2022)
Objectives The aim of this study was to compare the predictive capability of antral follicle count (AFC) and the anti-Müllerian hormone (AMH) on ovarian response in infertile women and to identify potential factors influencing retrieved oocytes. Methods A total of 2585 infertile women who underwent in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles had been enrolled in this study. Spearman correlation was used to investigate the correlation between retrieved oocytes and AFC. Multiple linear regression analysis was used to study the parameters affecting the number of retrieved oocytes. Results Spearman correlation and multiple linear regression analysis revealed that the oocyte retrieval number was positively correlated with AFC (r = 0.651, p < 0.001) and AMH (r = 0.566, p < 0.001) and negatively correlated with age (r = -0.425, p < 0.001) and regimen selection (r = -0.233 p < 0.001). There was no significant correlation between retrieved oocytes and BMI (p = 0.913). ROC analysis revealed that AFC was a better predictor of adverse effects than AMH, BMI, and age (AUC: 0.916 VS 0.791, 0.575, 0.752). Meanwhile, AFC and AMH were comparable in predicting high response (AUC = 0.731 and AUC = 0.733, respectively). Conclusions This study showed that retrieved oocytes were positively correlated with serum AMH and AFC and negatively correlated with age and BMI. AFC had an ideal predictive performance in ovarian response prediction. The mechanism of the effect of AFC on ovarian response during controlled ovarian hyperstimulation (COH) needs to be further investigated.